2017
DOI: 10.3847/1538-4357/aa65d0
|View full text |Cite
|
Sign up to set email alerts
|

The SCUBA-2 Cosmology Legacy Survey: Multi-wavelength Properties of ALMA-identified Submillimeter Galaxies in UKIDSS UDS

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
139
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 113 publications
(160 citation statements)
references
References 110 publications
(230 reference statements)
20
139
0
Order By: Relevance
“…Figure 2 shows the moment-zero maps with a uv-taper of 500 kλ (0 17×0 16) and compares the recovered [C II] emission to the spectra from the lower-resolution observations from ALMA Cycles 0 and 1 (Swinbank et al 2012;De Breuck et al 2014). Emission from [C II] was detected for UDS 47.0 as a very broad line at ∼351 GHz in the shallower 0 3 data from ALMA Cycle 1 (Simpson et al 2015b(Simpson et al , 2017. In our deeper 0 03 resolution observations, we detect a broad ∼4σ [C II] emission line.…”
Section: [C Ii] Emission Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows the moment-zero maps with a uv-taper of 500 kλ (0 17×0 16) and compares the recovered [C II] emission to the spectra from the lower-resolution observations from ALMA Cycles 0 and 1 (Swinbank et al 2012;De Breuck et al 2014). Emission from [C II] was detected for UDS 47.0 as a very broad line at ∼351 GHz in the shallower 0 3 data from ALMA Cycle 1 (Simpson et al 2015b(Simpson et al , 2017. In our deeper 0 03 resolution observations, we detect a broad ∼4σ [C II] emission line.…”
Section: [C Ii] Emission Linesmentioning
confidence: 99%
“…A pilot study observed the 30 brightest SCUBA-2 sources in the ∼1 deg 2 UKIDSS/UDS field (Simpson et al 2015a(Simpson et al , 2015b(Simpson et al , 2017. These 0 3 resolution ALMA observations revealed a serendipitous detection of [C II] emission at 350.78 GHz, establishing the redshift as z=4.420.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Although such strongly star-forming galaxies are rare in the local universe, the space density of bright SMGs (i.e., S 850μm >1 mJy, corresponding to a far-infrared luminosity, L IR 10 12 L  ) increases rapidly with look-back time and appears to peak at z∼2-3 (e.g., Barger et al 1999;Chapman et al 2005;Smolčić et al 2012;Yun et al 2012;Simpson et al 2014). Due to their potentially rapid formation, SMGs have been proposed to be the progenitors of spheroidal galaxies in the local universe (e.g., Lilly et al 1999;Swinbank et al 2006;Simpson et al 2014Simpson et al , 2017. They are also thought to be linked to quasi-stellar object (QSO) activity due the similarity of their redshift distribution to that of luminous QSOs (e.g., Coppin et al 2008), as well as being linked to compact red galaxies seen at z∼1-2 (e.g., Cimatti et al 2008;Whitaker et al 2012;Toft et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With angular resolution better than 1″ and thus subarcsecond positional precision, we are starting to obtain a more complete understanding of the multiwavelength characteristics of SMGs (e.g., Hodge et al 2013;Swinbank et al 2014Swinbank et al , 2015Thomson et al 2014;Aravena et al 2016;Walter et al 2016;Danielson et al 2017;Dunlop et al 2017;Simpson et al 2017;Wardlow et al 2017). However, for single-dish submillimeter surveys of fields in the northern sky, it is not possible to perform ALMA follow-up, and so we must rely instead on the use of the Submillimeter Array (SMA) or IRAM's Northern Extended Millimetre Array (NOEMA) to obtain interferometric identifications (e.g., Smolčić et al 2012;Hill et al 2018).…”
Section: Introductionmentioning
confidence: 99%